TINDAK TUTUR EKSPRESIF PADA TUTURAN GURU DALAM PROSES PEMBELAJARAN BAHASA INDONESIA DI SMAN BARENG JOMBANG - Fitri Resti Wahyuniarti; Nanda Risky Ardhana; Novita Dwi Lestari (Universitas Muhammadiyah Surabaya, 2025)
One way to guide students through the learning process to achieve learning ob jectives can be through teaching and learning activities. Learning should consider the individual characteristics of the students, as they are the ones who will be learning. Therefore, the purpose of education, implemented through the learning process, must be to bring about change in each student. The teacher's use of language and speech is one way to transform students and achieve learning objectives. In selecting expressive utterances, teachers must also ensure that what is conveyed is well received by students. Therefore, the purpose of this study is to describe the forms and manifestations of expressive speech acts in the ruru utterances in the Indonesian language learning process at SMAN Bareng Jombang. This research is a qualitative descriptive study with the following stages: initial observation, determining research objectives, data collection, data analysis, and drawing conclusions. The research data consists of teacher utterances indicated as expressive speech acts in the learning process. This research was conducted in grade XI of SMA Negeri Bareng Jombang. data collection, data reduction (Identification, Classification, Description), data presentation (Coding, Table Creation, Selection of affixation examples), and drawing conclusions (verification) by utilizing triangulation as a technique to check the validity of research findings. The results of this study found forms of expressive speech acts, including: expressive speech acts of expressing gratitude, happiness, apologizing, praising, complaining, criticizing, congratulating, and greeting.